The Dynamics of Water Resource Governance in Post-Omnibus Indonesia: Centralization, Sustainability, and Social Inclusion - Andi Setyo Pambudi; Bambang Pramujo (Contemporary Public Administration Review, 2026)
Water governance in Indonesia faces increasing complexity due to urbanization, climate change, and regulatory fragmentation. Although water is a philosophical entity in sustaining life and development, its management continues to suffer from gaps between policy and field-level implementation. This study is urgent in light of the Job Creation Law (Omnibus Law), which has significantly amended sectoral regulations related to water resources, yet its impact on water resilience and sustainable development remains underexplored. The objective of this research is to evaluate how the Omnibus Law influences water governance, particularly in balancing social, economic, and environmental sustainability. A qualitative approach is employed, using document analysis, selected watershed case studies, and Focus Group Discussions (FGDs) with multi-sector stakeholders. Findings reveal that the Omnibus Law promotes centralization of authority, simplifies licensing procedures, and encourages private sector involvement, but risks weakening environmental safeguards and widening inequalities in water access. Key recommendations include the need for a more inclusive and adaptive policy framework, stronger intersectoral coordination, and active community participation in watershed management as a strategy to achieve long-term water resilience.